Chemically-mediated attraction of three parasitoid species to mealybug-infested cassava leaves - Bertschy, C; Turlings, TCJ; Bellotti, Anthony C.; Dorn, S. (1997)
We investigated whether cassava plants that are infested by the cassava mealybug, Phenacoccus herreni (Pseudococcidae, Sternorrhyncha), emit attractants for the encyrtid parasitoids Aenasius vexans Kerrich, Apoanagyrus (Epidinocarsis) diversicornis Howard, and Acerophagus coccois Smith. Bioassays with a Y-tube olfactometer showed for all three species that female wasps were most responsive and selective when they were 1.5 to 2.5 days old. Females of these age groups were used to test their ability to distinguish between the odor of plants with and without mealybugs. The wasps were offered choices between infested cassava leaves vs. healthy ones, infested leaves vs. clean air, and healthy leaves vs. clean air. A. vexans and A. diversicornis were strongly attracted to infested leaves and preferred these over healthy ones. In contrast, A. coccois was significantly attracted to either healthy or infested leaves, and did not distinguish between the two. The results suggest that A. coccois, which has the broadest known host range of the three, may be responsive only to general plant odors, while A. vexans and A. diversicornis respond more specifically to odors associated with mealybug infestation.